Electrodeposition of Nanostructured Cobalt Films from Choline Chloride-Ethylene Glycol Deep Eutectic Solvent. Issue 11 (11th September 2018) - Panzeri, G.; Pedrazzetti, L.; Rinaldi, C.; Nobili, L.; Magagnin, L.
Abstract : Among the Deep Eutectic Solvents (DESs), ethylene glycol-based one is attracting the attention of many researchers because of its relatively low viscosity with respect to analogous eutectic systems with urea, malonic acid or glycerol. In this work, the electrochemical behavior of Co(II) in a eutectic solution of choline chloride and ethylene glycol (1ChCl:2EG molar ratio) was investigated by cyclic voltammetry (CV) at 70°C followed by galvanostatic deposition (GD). The deposits on copper substrate were characterized with a field emission scanning electron microscope (FE-SEM) showing a nanostructured surface texture with platelet-like architecture resulting in a high hydrophobicity (contact angle CA >135°). By increasing the current density, more compact films were obtained while the addition of boric acid resulted in a finer structure. X-ray diffraction (XRD) analysis determined the coexistence of FCC and HCP phases, both with and without the addition of boric acid to the bath. Annealing in a nitrogen atmosphere was performed at different temperatures (300°C–600°C) to observe microstructure evolution. Magnetic properties with a coercivity of 60–80 Oe were measured by means of micro-indentation and Vibrating Sample Magnetometer (VSM).